2013
DOI: 10.1155/2013/131647
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Residues in Sediments and Waters from Cocoa Producing Areas of Ondo State, Southwestern Nigeria

Abstract: This study investigated levels of organochlorine pesticide (OCP) residues in water and sediment samples from eleven rivers serving as drinking water sources and receiving runoff from nearby cocoa plantations in Ondo State, Nigeria. Twenty-two composite samples of surface water and sediments (0–3 cm) were collected randomly using grab technique and replicated thrice per season. The efficiency of the two techniques [supercritical fluid extraction (SFE) and liquid/liquid extraction (LLE)] was evaluated with perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
4
28
3
1
Order By: Relevance
“…Concentrations reported of the HCH isomers in this research in the Alvarado lagoon system were lower than those found in the state of Ondo, Nigeria, with the following concentrations: α-HCH: not detected (ND): <0.02 µg g −1 ; 8.07 ± 3.00; β-HCH: ND: 10.91 ± 6.66 µg g −1 ; γ-HCH: ND: 9.08 ± 0.02 µg g −1 [32]. Additionally, in the Densu River in Ghana, maximum sediment concentrations for γ-HCH (0.555 ± 0.12 µg kg −1 and 0.608 ± 0.24 µgk −1 ) and δ-HCH (0.140 ± 0.05 and 0.14 ± 0.01 µg kg −1 ) have been reported.…”
Section: Hexachlorocyclohexane (Hch)contrasting
confidence: 77%
See 1 more Smart Citation
“…Concentrations reported of the HCH isomers in this research in the Alvarado lagoon system were lower than those found in the state of Ondo, Nigeria, with the following concentrations: α-HCH: not detected (ND): <0.02 µg g −1 ; 8.07 ± 3.00; β-HCH: ND: 10.91 ± 6.66 µg g −1 ; γ-HCH: ND: 9.08 ± 0.02 µg g −1 [32]. Additionally, in the Densu River in Ghana, maximum sediment concentrations for γ-HCH (0.555 ± 0.12 µg kg −1 and 0.608 ± 0.24 µgk −1 ) and δ-HCH (0.140 ± 0.05 and 0.14 ± 0.01 µg kg −1 ) have been reported.…”
Section: Hexachlorocyclohexane (Hch)contrasting
confidence: 77%
“…The presence of a higher concentration of organochlorine pesticides in sediments with respect to the concentrations was found in the analyzed water samples, which is why it is important to analyze the sediment matrix [32]. The presence of organochlorine compounds represents an environmental risk because of their bioaccumulation in the food chain and the alteration of aquatic ecosystems in both fresh and coastal waters [7,11].…”
Section: Sediments As a Source Of Pollutant Distributionmentioning
confidence: 99%
“…Table 1 showed the results of the various OCPs residues in water samples from the studied area. As may be seen, α-BHC, endosulfan I and endrin were below the detection limit ( The results indicated higher concentrations of organochlorine pesticide residues in the water samples when compared with previous results from the same river in the Ondo State axis (Idowu et al, 2013;Okoya et al, 2013). According to Okoya et al (2013), sixteen OCPs residues (HCB, α-BHC, β-BHC, ϒ-BHC, heptachlor, aldrin, trans-chlordane, cis-chlordane, α-endosulfan, β-endosulfan, p, p'-DDE, o, p'-DDD, p, p'-DDD, p, p'-DDT, dieldrin and endrin) were not detected in Ogbese river.…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 46%
“…As may be seen, α-BHC, endosulfan I and endrin were below the detection limit ( The results indicated higher concentrations of organochlorine pesticide residues in the water samples when compared with previous results from the same river in the Ondo State axis (Idowu et al, 2013;Okoya et al, 2013). According to Okoya et al (2013), sixteen OCPs residues (HCB, α-BHC, β-BHC, ϒ-BHC, heptachlor, aldrin, trans-chlordane, cis-chlordane, α-endosulfan, β-endosulfan, p, p'-DDE, o, p'-DDD, p, p'-DDD, p, p'-DDT, dieldrin and endrin) were not detected in Ogbese river. Previous and current use of the pesticides, run-off from various agricultural areas, washing of materials or containers after pesticide application, environmental factors, nature and fate of pesticides in an aquatic environment could all have contributed to the current levels of the OCPs in the river.…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 46%
“…In a study from Nigeria, most of the target OCPs analysed were reported not to be detected above the detection limits in the majority of the river water samples, as was also found in the present study (Okoya et al 2013) but with higher reported concentrations of 1.51, 0.11, 0.13 and 0.13 g/L for dieldrin, p,p'-DDE, cis-chlordane and -endosulfan, respectively (Okoya et al 2013). No data are available from studies done elsewhere in Africa to indicate the risk level to aquatic organisms from OCPs, but the number and type of detections suggest that there are similarities in the OCP detections in different areas in Africa.…”
Section: Pesticide Use and Pec Values For The Nine Pesticides Used Bysupporting
confidence: 83%